Teaching Philosophy Statement for Physics Teachers: Letâ€™s Think About - Sumardani, D.; Dujali, C. C. (Jurnal Pendidikan IPA Indonesia, 2021)
The statement of teaching philosophy reflects on teachersâ€™ growth and dedication to achieve the goal and values. Concerning philosophy, physics is the most fundamental science discipline which has profound philosophical implications. This article aims to discuss the importance of the teaching philosophy statement (TPS) for sustaining the teaching-learning process in the classroom. Moreover, it also includes the authorsâ€™ TPS in teaching physics. This academic paper employs the systematic literature review and narrative literature review to explain scholarly opinion regarding teaching philosophy among physics and natural sciences philosophers. Three educational implications have been discussed. First, educators need to realize that not every student wants to be a physicist, and teachers need to manage this problem. More often, the physics teachers also have to think about addressing students with different abilities in the classroom. Second, as the facilitator of the learning outcomes, the teachers must possess good character and value-laden attributes necessary for teaching. Finally, the researchers of this study provide the TPS for physics, â€œLet Us Think About,â€ and philosophical implications in teaching physics. The term of teaching philosophy may vary based on the expert who writes it and its application in the classroom (i.e., philosophy in science teaching, philosophy of physics, philosophy of science in teaching, teaching philosophy, teaching statement, and teaching philosophy statement). However, the teaching philosophy statement is the most common phrase since Beatty et al. explain the concept in the early 21st century. In addition, the finding indicates that TPS is important for developing teachersâ€™ way of thinking in the classroom setting.